2019
DOI: 10.1136/bmjopen-2018-027147
|View full text |Cite
|
Sign up to set email alerts
|

Where there is no nurse: an observational study of large-scale mentoring of auxiliary nurses to improve quality of care during childbirth at primary health centres in India

Abstract: ObjectiveClinician scarcity in Low and Middle-Income Countries (LMIC) often results in de facto task shifting; this raises concerns about the quality of care. This study examines if a long-term mentoring programme improved the ability of auxiliary nurse-midwives (ANMs), who function as paramedical community health workers, to provide quality care during childbirth, and how they compared with staff nurses.DesignQuasi-experimental post-test with matched comparison group.SettingPrimary health centres (PHC) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
(23 reference statements)
3
24
0
Order By: Relevance
“…Thus, our study supports the argument of Close To Community (CTC) potential of FHWs for expanding the utilisation of MCH services especially among the poor women, which often stand at the fringes of the health system [7,53,55]. Our findings are in keeping with previous studies that examined the role of FHWs in improving MCH care [21,22,24,27,41], and microlevel investigations in India [13,14,18,30,31,41,45].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, our study supports the argument of Close To Community (CTC) potential of FHWs for expanding the utilisation of MCH services especially among the poor women, which often stand at the fringes of the health system [7,53,55]. Our findings are in keeping with previous studies that examined the role of FHWs in improving MCH care [21,22,24,27,41], and microlevel investigations in India [13,14,18,30,31,41,45].…”
Section: Discussionsupporting
confidence: 90%
“…However, enhancing engagement with FHWs can be just as cost-effective, results-driven and are shown to be a proven intervention for bringing equity in MCH care and outcomes [28,56]. However, previous studies have reported that factors such as a lack of skills, low qualifications, the multitasking nature of their job, low incentives, and low recognition is discouraging many FHWs from remaining in this profession [40,42,44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigorous program evaluations were conducted to assess the impact of AMANAT. In a pre-post test comparison, proportional (percentage point) post interventional increases in correct actions taken by ANMs were 17.5 (95% CI 14.8 to 20.2) for managing normal deliveries, 25.9 (95% CI 22.4 to 29.4) for postpartum hemorrhage, and 28.4 (95% CI 23.2 to 33.7) for neonatal resuscitation [ 6 ]. Another similar evaluation revealed that the impact was mostly sustained, with correct intrapartum practices during normal delivery slightly changing from 44.2% (95% CI: 42.1 to 46.4) when mentoring in the last three months to 39.1% (37.7–40.5) one year post-mentoring [ 20 ].…”
Section: Learning From International Experiencementioning
confidence: 99%
“…The purpose of this ‘capacity-building’ article is to share our collective (and ongoing) experience in implementing and evaluating the world’s largest program. This is particularly important as large-scale programs present different kinds of challenges to public health practitioners and program managers [ 6 ]. In so doing, we point to a number of areas for further research and suggest implications for others designing comparable programs.…”
Section: Introductionmentioning
confidence: 99%